Development of highly selective electronic nose using molecular imprinted polymer (MIP) for recognition of fruit ripeness - Huzein Fahmi, Hawari; N. M., Samsudin; Mahmad Nor, Ahmad, Prof. Madya Dr.; Ali Yeon, Md Shakaff, Prof. Dr.; Supri A., Ghani, Prof. Madya Dr.; Yufridin, Wahab, Dr.; Uda, Hashim, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.